The Relationship of Pregnancy Anemia with Primary Postpartum Hemorrhage in Tarakan, North Kalimantan - Ririn Ariyanti; Selvia Febrianti; Ely Rahmawati (Green Publisher Indonesia, 2022)
Bleeding in childbirth is caused by anemia in pregnancy. This happens because when the mother gives birth, there will be adequate uterine contractions to be born. This study aims to determine the relationship between anemia during pregnancy and the incidence of primary postpartum hemorrhage. This type of research is analytical survey research. The subjects in this study were all pregnant women who suffered from anemia. The research place of the Juata Community Health Center in Tarakan City, North Kalimantan. From May to June 2020. The data used in this study is secondary data obtained from medical record books at the Juata Community Health Center. This study used a total sampling technique—data analysis using chi-square analysis. The statistical tests showed that pregnant women with anemia had an 11,253 times greater risk of bleeding during childbirth than women who gave birth vaginally. Pregnant women and their families should take care of their pregnancy by routinely carrying out antenatal care under antenatal care service standards